Socioeconomic position over the life course and impaired lung function of older adults in Central and Eastern Europe: the HAPIEE study - Quispe-Haro, Consuelo; Pająk, Andrzej; Tamosiunas, Abdonas; Capkova, Nadezda; Bobak, Martin; Pikhart, Hynek (Journal of epidemiology and community health, 2022)
BACKGROUND: Social differences in lung functioning have been reported, but the role of socioeconomic position (SEP) at different stages of life is less well understood, particularly in Central and Eastern Europe. This study addressed this question. METHODS: The analysis included 10 160 individuals aged 45-70 years from the Czech Republic, Poland and Lithuania. Lung function was either normal if values of forced expiratory volume in the first second divided by forced vital capacity (FEV1/FVC) and FVC were higher than the lower limit of normality or impaired if otherwise. SEP at three stages of life was assessed using maternal education (childhood), participant's education (young adulthood), and current ability to pay for food, clothes and bills (late adulthood). SEP measures were dichotomised as advantaged versus disadvantaged. The associations between impaired lung function and life-course SEP were estimated by logistic regression. RESULTS: Disadvantaged SEP in young and late adulthood had higher odds of impaired lung function. In young adulthood, age-adjusted ORs were 1.26 (95% CI 1.06 to 1.49) in men and 1.56 (95% CI 1.29 to 1.88) in women, while in late adulthood, the ORs were 1.15 (95% CI 0.99 to 1.34) in men and 1.26 (95% CI 1.09 to 1.46) in women. Men and women disadvantaged at all three stages of life had ORs of 1.42 (95% CI 1.06 to 1.91) and 1.83 (95% CI 1.32 to 2.52), respectively, compared with those always advantaged. Smoking substantially attenuated the ORs in men but not in women. CONCLUSION: Reducing socioeconomic inequalities in young and late adulthood may contribute to reducing the risk of impaired lung function in late adulthood.
Keywords: life course epidemiology; health impact assessment; epidemiology; health inequalities; social class